PENGAWASAN TERHADAP PENYALAHGUNAAN WEWENANG POLRI MENGADAKAN TINDAKAN LAIN MENURUT HUKUM YANG BERTANGGUNG JAWAB (DISKRESI) - Suteja, Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 2 (2013), 2013)
ABSTRACT Function of control and authority of the Police of the Republic of Indonesia related to the aspects of preemptive, preventive, and repressive. One of duties of the Police of the Republic of Indonesia as the state's instrument and law enforcer in maintain the law repressively to help the Department of Justice especially in the field of criminal law the Police as the investigator and investigating offrcer can carry out other action according to law which is responsible or discretion. The formal legalistically arrangement about the police discretion in KUHAP (Article 5 subsection (1) letter a number 4 and Article 7 subsection (1) letter j) and the Law No.2 1n2002 about the Police of the Republic of Indonesia in Article 16 subsection (1) letter I and subsection (2) and Article 18 subsection (1) and subsection (2) which is written and implicated widely so it makes this become a blur norm of law, and it needs an interpretation in the application. The discretion arrangement seems to emerge the disharmonious of law norm. To avoid the deviation of the discretion implementation in the future the norm arrangement has to be harmonized through the law construction to the articles of the arrangement by reevaluating and reformulating them by the legislative institution. The type ofresearch to be used to research the substance of discretion by the police in this scientific work is the normative law research or doctrinal law research. Police discretion needs an internal and extemal monitoring from the related institution including monitoring ftom the society especially the victim. Deviation of discretion will emerge a risk due to law and law responsibility by the person who does the discretion. The law responsible can be a responsibility of criminal, civil Iaw and administration law. Deviation of discretion action as the result of the wide range of discretion scope and there is no measurement or criterion of discretion forms that can be done by the Police as a reference in action which is arranged in legislation. The study and analysis of police discretion upon the problems presented is reviewed by the law principles, expertise doctrine, formal basic and law theories such as law system theory, law harmonious theory, progressive law theory, authority theory and monitoring theory. The theoretical perspective study is supported by empirical law materials and descriptive description of the writer.
Keywords: control; discretion; police